Biochemical description of fresh produce quality factors - Fellman, John K.; Michailides, Themis J.; Manganaris, George A. (My University, 2013)
Purpose of review: Consumer appreciation of nutritional value and putative disease prevention roles has fostered worldwide increases in fresh fruit consumption. Preservation of fresh fruit quality remains a postharvest challenge for the perishables industry. Many biochemical factors influence the consumer's perception of quality. Using examples from widely studied fruits, this review focuses on recent developments in general areas associated with quality assessment, and quality changes in the postharvest environment. Recent findings: The principal biochemical components that contribute to the consumer perception of quality can be separated into three major classes: (1) those associated with “mouth feel”, ie, firmness and texture; (2) those associated with taste, eg, sweetness, acidity, aroma/flavor, and astringency ; and (3) those components that contribute to appearance, notably color and surface finish. Objective measurement of texture is possible using a variety of destructive instrumentation, with progress in development of non-destructive technologies with possible on-line applications. Our understanding of cell wall architecture and biochemical components therein has advanced, establishing the relationship between cell wall modifying enzymes and textural softening. Sensory correlations between several types of objective measurements are still being investigated. Advanced sweetness and acidity measurement technologies are well-developed, with many studies regarding postharvest changes and the influence on sensory quality. Volatile aroma production remains an active area of investigation, both in the analytical and sensory disciplines. Postharvest storage and handling influence volatile development. Phenolic substance measurement has enjoyed renewed popularity due to the putative neutraceutical benefits, with more emphasis on radical scavenging capability. Exploitation of genomic and biotechnological tools (gene isolation, cloning and expression studies) has resulted in initial quality trait heritability studies. Limitations: Challenges still remain. Fruit eating quality factors are very complex traits that are influenced by the interaction of genome, growing conditions, and harvest maturity, as well as postharvest handling and storage. Fundamental mechanisms responsible for changes in quality are not completely understood, as most biochemical pathways that determine quality traits are still being identified. Directions for future research: Consumer perception of fruit quality by consumer sensory analysis, combined with instrumental analysis should further define the relationship of individual components responsible for texture, taste and aroma to the total “quality experience”. This includes the role of changes in cell wall components, turgor, sugar and acid transformations, and volatile aroma compound changes in relation to instrumental and sensory testing. Through application of biochemical, genomic, proteomic and microscopic methods to determine fundamental metabolism and its control, the true nature of "ripeness", "eating quality" and "freshness" of fruit products will be revealed, facilitating employment of modern storage and handling technologies for preservation of same.
Keywords: Cell Wall; Firmness; Texture; Color; Taste; Astringency; Aroma; Perishable; Phenolics; Phytochemicals; Antioxidants